Review—The Current and Emerging Applications of the III-Nitrides. (22nd November 2017) - Zhou, Chuanle; Ghods, Amirhossein; Saravade, Vishal G.; Patel, Paresh V.; Yunghans, Kelcy L.; Ferguson, Cameron; Feng, Yining; Kucukgok, Bahadir; Lu, Na; Ferguson, Ian T.
Abstract : III-Nitrides are attracting considerable attention as promising materials for a wide variety of applications due to their wide coverage of direct bandgap range, high electron mobility, high thermal stability and many other exceptional properties. The light-emitting diodes based on III-Nitrides revolutionize the solid-state lighting industry. III-Nitrides based solar cells and thermoelectric generators support the sustainable energy progress, and the III-Nitrides are better alternatives for power and radio frequency (RF) electronics compared with silicon. The doped III-Nitrides' magnetic properties and sensitivity to radiation can contribute to novel spintronic and nuclear detection devices. This paper will review III-nitride material properties and their corresponding applications in LEDs, solar cells, power and radio frequency (RF) electronics, magnetic devices, thermoelectrics and nuclear detection. The typical values of electrical, optical, thermoelectric, magnetic properties are cited, the current state of art investigations are reported, and the future applications are estimated.